Інфраструктурне забезпечення організації логістичної діяльності підприємств харчової промисловості україни у контексті продовольчої безпеки - Трушкіна, Н. В.; Пушак, Я. Я. (Odesa National University of Technology, 2023)
The article provides an economic analysis and forecasting of the dynamics of the main indicators ofthe functioning of business entities in the food industry of Ukraine. On the basis of the performed analysis, the key obstacles to the organization of logistics activity processes, which are connected with the full-scale invasion of Russia on the territory of Ukraine, have been determined; unstable political and economic situation; threats to energy and national security; deterioration of the foreign economic situation and investment climate; blockade of seaports; limited amount of financial resources; damage to infrastructure facilities; the growth of pollutant emissions; insufficient use of digital and information and communication technologies. It has been substantiated that in order to eliminate the listed barriers, it is expedient to form the proper infrastructural support for the organization of logistics activities of food industry enterprises based on the creation of a cluster structure as a form of cooperation between authorities, institutions of critical infrastructure (transport, logistics, innovation, information, agro-industry, food, etc.), institutions and organizations of the business, scientific and educational environment. It has been established that for this it is necessary to define such appropriate institutional, organizational and financial conditions as the improvement of regulatory and legal regulation of the development of the food industry, the agro-industrial complex, the transport sector and the organization of logistics activities; introducing changes and additions to the Concept of creating clusters in Ukraine, regional development strategies until 2027 regarding the creation of cluster structures as a business entity in the food industry; development of the Strategy for the comprehensive development of the food industry in the economic regions of Ukraine, taking into account the specifics of their functioning; development and implementation of organizational, economic and financial mechanisms for managing cluster development in the food industry using circular economy tools, green logistics, digital technologies and information systems; development of the Concept of the development of critical infrastructure in the context of the restoration of the food industry in the context of the strategy of post-war development and resilience of the national economy of Ukraine.